Kenesbay Abdullayev: Creative Activities and its Role in the Development of Bayan Art of Karakalpakstan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article reveals the facets of the activities of the Honored Art Worker of the Republic of Karakalpakstan, Excellent Worker of Public Education of the Uzbek SSR K. Abdullayev as a musician-performer, educator-teacher, composer-melodist and conductor, and founder of the development of the art of bayan.